The Effect of Earning Per Share, Company Size, and Liquidity on Company Value in LQ-45 Companies - Setyowati, Lina; Sudarwati, Sudarwati (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Economic growth in this era of rapid globalization, the economy has a very important role. Economic or business development What causes every company to compete to maximize profits generated to increase the value of the company. This study aims to examine and analyze the effect of Earning Per Share, Company Size, and Liquidity on Company Value. The population in this study are all companies that are included in the LQ 45 index companies listed on the IDX in 2019-2021. A total of 15 companies were taken using the purposive sampling technique. Testing the hypothesis in this study using multiple linear regression text. The result of this study indicates that Earning Per Share has a significant effect on company value. Company Size does not affect company value. Meanwhile, Liquidity has a significant influence on company value.